Acute Hepatitis Secondary to the Use of Ilex paraguariensis (Mate Tea): A Case Report and Review of Literature. (13th October 2019) - Rodriguez, Eduardo A.; Teixeira Yokoda, Raquel; Payton, David E.; Pai, Rish; Byrne, Thomas J.
Abstract : Drug induced liver injury is a very frequent cause of hepatotoxicity and within that group, herbal and dietary supplements are a well described subcategory. The following clinical vignette describes the case of a young man with acute hepatitis secondary to the use of Ilex paraguariensis, also known as yerba mate, which is a herbal product commonly drunk in South America. This is the first written case of mate tea induced hepatotoxicity.